Assessment of Cardiac Blood Pools in Radiocardiography by Various Indicator Dilution Models - Olkkonen, H.; Penttilä, I. M. (Nuklearmedizin - NuclearMedicine, 1977)
Heart blood pools were evaluated by different indicator dilution models from single detector 113mIn radiocardiographic measurements on healthy subjects. It appeared that generally accepted mathematical expressions based on the nth moments of the radiocardiographic dilution curve overestimate the heart volumes by 30–40%. The study suggests that the indicator dispersion within the heart chambers is an dilution process, which ought to be included in the radiocardiographic models. Dispersion models based on the random walk equation, probability density function and the gamma variate model produced consistent heart volumes. The suitability of the dispersion models for clinical routine use is discussed briefly.